Disinformation in the EU Law: Moral Theories and the Context - Johanas Baltrimas (Law: Journal of the University of Latvia)
In recent years, there have been scandalous cases of information warfare acts in the Western world committed by hostile foreign governments. The effect of such acts is dramatically amplified by the widespread use of the internet media and ongoing military conflicts. Accordingly, the EU has taken steps in the battle against disinformation. The legal definition of disinformation contains attributes that need further explanation, particularly, lying and deception. Philosophical theories contain valuable insights on the morality of lying and deception, which can be adapted for interpretation of the disinformation concept.